Independensi Notaris dalam Melaporkan Dugaan Tindak Pidana Pencucian Uang yang Dilakukan oleh Penghadap - Aulia Khairunisa; M. Sudirman; Benny Djaja (Badan Penerbit STIEPARI Press, 2024)
This study aims to analyze the independence of notaries in reporting suspected money laundering (TPPU) committed by the complainant (client) in notarial practice. The main problem in this study is the form and limits of notary independence in carrying out reporting obligations on suspicious financial transactions that potentially contain elements of TPPU. This study uses a normative legal research method with a statutory approach to examine the legal provisions governing the obligations and legal protection for notaries, and a conceptual approach to describe the doctrines and theories related to professional independence, the principle of professional secrecy, and legal protection. The data used are secondary data obtained through literature studies, including primary, secondary, and tertiary legal materials which are then analyzed qualitatively through legal interpretation and legal argumentation. The results of the study indicate that notary independence in reporting suspected TPPU is in a complex position because it must balance the obligation to maintain professional secrecy with the obligation to report to the relevant authorities. This independence is realized through compliance with statutory provisions and the principle of prudence as a form of legal protection for notaries.